Food security – Status and determinants – During the COVID-19 lockdown: Evidence from primary survey in eastern India - Kumar, Anjani; Sonkar, Vinay Kumar; Srinivasa, Aditya Korekallu (International Association of Agricultural Economists, 2021)
Lockdowns induced by COVID-19 have threatened food security in most developing countries. Four weeks after the country went into lockdown, we carried out a telephone survey of roughly 2,600 rural households in eastern India, one of the poorest regions of the world. The aim was to provide rapid evidence on the status and determinants of food insecurity and to understand the coping strategies adopted by rural households during the pandemic. Using comprehensive telephone survey data from 2,599 households, we estimated the status of food insecurity using the Food Insecurity Experience Scale. We found that roughly 98 percent of rural households reported a negative income shock after countrywide lockdown was imposed. We further observed that about 46 percent of the sampled households were moderately food insecure and 25 percent were severely food insecure. We also observed regional differences in the extent of food insecurity. The results of the Poisson regression indicate that households that belong to lower social strata and have less land and fewer years of education are more likely to suffer from food insecurity. The results also indicate that households which are receiving government assistance are more likely to be food secure.